Paper-Based vs. Digitalized Glossaries in Laboratory Scripts - Jenna Koenen; Lars Mariot; Rüdiger Tiemann (Foxton Books, 2023)
Abstract: In the future, learning will be essentially characterized by the ability to regulate the learning process and monitor success independently from a teacher. The technical possibilities offer better access to learning contents, precise and more individualized feedback, and learning phases adapted precisely to the needs of the learner in terms of scope and pace. In this study, we investigate an important aspect of the digitization of teaching/learning processes using the example of laboratory scripts for chemistry students at university. The focus is on looking up terms and concepts in preparation for the lab internships, firstly in a paper-based glossary and secondly in a digital glossary. During a two-day study, a total of 16 students prepared for experiments on two topics with completely identical materials. We then studied the influence of content knowledge, motivation, and cognitive load. While all students show significant learning achievements, there are no significant differences between the groups. Furthermore, results show that pure digitization of information has no effect, despite the theoretically assumed advantages.